Profiles Of Deliberate And Accidental Self Harmers Admitted In Hospitals In Malaysia Project Report (PRODASH) - Firdaus Datuk Abdul Gani; Norizam Alias; Suria Hussin; Zuraida Ahmad; Norhayati Ali; Jamaiyah Haniff; Lazli Bakar; Izzat Tajjudin; Nadeeya Umaisara Mohamad Nor (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by SCOPUS